The influence of different examiners on the Body Condition Score (BCS) in South American camelids—Experiences from a mixed llama and alpaca herd - Wagener, Matthias Gerhard; Schregel, Johannes; Ossowski, Nina; Trojakowska, Anna; Ganter, Martin; Kiene, Frederik (Frontiers in Veterinary Science, 2023)
Particularly in unshorn llamas and alpacas with a dense fiber coat, changes in body condition often remain undetected for a long time. Manual palpation of the lumbar vertebrae is hence a simple and practical method for the objective assessment of body condition in South American camelids (SAC). Depending on tissue coverage, a body condition score (BCS) of 1 (emaciated) to 5 (obese) with an optimum of 3 is assigned. To date, there is a lack of detailed information on the comparability of the results when the BCS in llamas or alpacas is assessed by different examiners. Reliability of BCS assessment of 20 llamas and nine alpacas during a veterinary herd visit by six examiners was hence evaluated in this study. A gold standard BCS (gsBCS) was calculated from the results of the two most experienced examiners. The other examiners deviated by a maximum of 0.5 score points from the gsBCS in more than 80% of the animals. Inter-rater reliability statistics between the assessors were comparable to those in body condition scoring in sheep and cattle (r=0.52-0.89; τ=0.43-0.80; κw=0.50-0.79). Agreements were higher among the more experienced assessors. Based on the results, the assessment of BCS in SAC by palpation of the lumbar vertebrae can be considered as a simple and reproducible method to reliably determine nutritional status in llamas and alpacas.